2015
DOI: 10.1016/j.yhbeh.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Nesting behavior is associated with VIP expression and VIP–Fos colocalization in a network-wide manner

Abstract: Many species, including humans, engage in a series of behaviors that are preparatory to the arrival of offspring. Such "nesting behaviors" are of obvious importance, but relevant neuroendocrine mechanisms remain little studied. We here focus on the potential roles of vasoactive intestinal polypeptide (VIP) in the performance of appetitive and consummatory nesting behaviors in male and female zebra finches (Taeniopygia guttata). Using combined immunocytochemistry for Fos and in situ hybridization for VIP, we no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 98 publications
(174 reference statements)
1
11
0
Order By: Relevance
“…In addition to the vasotocin, mesotocin, and dopaminergic systems we have already sampled, it seems likely that other hormone signalling pathways such as vasoactive intestinal polypeptide (VIP) play an important role in the modulation of nest-building behaviour. For example, neuronal activity in VIP-immunopositive neuron populations correlates with nest-building behaviour (Kingsbury et al 2015 ), while prolactin under the control of VIP is important for brooding behaviour (Angelier and Chastel 2009 ) and plays an evolutionarily conserved role in parental behaviour across vertebrates. There is also evidence that steroids may also regulate the production of nest-building behaviour as female canaries treated with exogenous oestradiol expressed nest-building actions, even in the absence of nest material (Hinde and Steel 1976 ).…”
Section: Future Directions In Behavioural Neuroscience and Nest Buildmentioning
confidence: 99%
“…In addition to the vasotocin, mesotocin, and dopaminergic systems we have already sampled, it seems likely that other hormone signalling pathways such as vasoactive intestinal polypeptide (VIP) play an important role in the modulation of nest-building behaviour. For example, neuronal activity in VIP-immunopositive neuron populations correlates with nest-building behaviour (Kingsbury et al 2015 ), while prolactin under the control of VIP is important for brooding behaviour (Angelier and Chastel 2009 ) and plays an evolutionarily conserved role in parental behaviour across vertebrates. There is also evidence that steroids may also regulate the production of nest-building behaviour as female canaries treated with exogenous oestradiol expressed nest-building actions, even in the absence of nest material (Hinde and Steel 1976 ).…”
Section: Future Directions In Behavioural Neuroscience and Nest Buildmentioning
confidence: 99%
“…As observed by Ortiz-Ceballos, Hernández-García & Galindo-González (2009) , and Buch et al (2011) both in the field collections and the laboratory, here we found that P. corethrurus uses soil and mucus to construct nests with its mouth that are similar to those constructed in diapause by Millsonia anomala ( Blanchart et al, 1997 ) and Martiodrilus carimaguensis ( Jiménez et al, 2000 ). It has been suggested that nest architecture has evolved for multiple uses where the exterior layer acts to conceal the nest from predators and protect it from rain while the internal layer isolates it from temperature extremes, flooding, desiccation and hypoxia ( Mori & Chiba, 2009 ; Smiseth, Kölliker & Royle, 2012 ; Kingsbury et al, 2015 ). The nests constructed here could be a form of parental care to protect the cocoons from abiotic (reducing water loss and improving gas exchange) and biotic (predators) threats ( Ortiz-Ceballos, Hernández-García & Galindo-González, 2009 ), since the interior layer comprises a compacted wall formed by small soil particles bound together by mucus produced by the earthworm, while the exterior layer acts to disguise the presence of the nest.…”
Section: Discussionmentioning
confidence: 99%
“…The weak labeling of VIP in the telencephalon of blue tits, especially in the song system, can also be ascribed to interspecific differences in song learning, but also to the fact that courtship songs are less frequent during parental care (Hill et al, 2005 ). VIP is the releaser of prolactine, the hormone responsible for physiological and behavioral changes during parental care and also a neuromodulator, itself associated with parental behavior (Badyaev and Duckworth, 2005 ; Kingsbury et al, 2015 ). Intense expression of VIP in the bed nucleus of stria terminalis is in harmony with the parenting stage of blue tits in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in VIP immunoreactivity, as well as in VIP receptor gene expression have been identified in the hypothalamus of pigeons and hens in relation to the reproductive cycle (Cloues et al, 1990 ; Chaiseha et al, 2004 ). A recent study in zebra finch underlines the activation of VIP expression during nesting behavior (Kingsbury et al, 2015 ). VIP is also modulating the nesting behavior in hens and turkeys (Macnamee et al, 1986 ; Prakobsaeng et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%